2018
DOI: 10.1039/c8sm01288a
|View full text |Cite
|
Sign up to set email alerts
|

Nanoliter deposition on star-shaped hydrophilic–superhydrophobic patterned surfaces

Abstract: Nanoliter sized droplet deposition has gained increasing importance in many biomedical, chemical, and microfluidic applications and in materials synthesis. In this paper, we report a simple method for rapid and high-throughput deposition of nanoliter-sized droplets by dragging a larger droplet on star-shaped hydrophilic-superhydrophobic patterned surfaces. Dragging a droplet on the patterned surface causes water to adhere to hydrophilic patterns. As the larger mother droplet detaches from a star-shaped pattern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…17,18 Chang et al, studied the mobility of a nanoliter water droplet being dragged over a hydrophilicsuperhydrophobic patterned surface. 19 The authors observed preferential wetting on the hydrophilic patches, with small daughter droplets being formed when the droplet was dragged over those patches.…”
Section: 𝐿 𝑚 𝐿 𝑙mentioning
confidence: 99%
“…17,18 Chang et al, studied the mobility of a nanoliter water droplet being dragged over a hydrophilicsuperhydrophobic patterned surface. 19 The authors observed preferential wetting on the hydrophilic patches, with small daughter droplets being formed when the droplet was dragged over those patches.…”
Section: 𝐿 𝑚 𝐿 𝑙mentioning
confidence: 99%
“…[9][10][11][12][13][14][15][16][17][18][19] Over the years, various research groups have developed biomimicked antiwetting interfaces ranging from a few nanometers thickness to bulk antiwetting materials for a wide range of applications in energy, healthcare, and environmental remediation. [21][22][23][24][25][26][27][28][29][58][59][60][61][62] Lithography, 63,64 plasma/chemical etching, 65,66 templation, 67,68 and electrospinning approaches 69,70 have often been adopted to construct different types of hierarchal topography, while various chemistries have been exploited to fulfil the low or high surface energy requirements. 6 There are numerous research articles and review papers that elaborate the aforementioned subjects.…”
Section: Bio-mimicked Antiwetting Interfaces: Weighing the Importance...mentioning
confidence: 99%
“…19,20 However, instead of decorating the hierarchical topography with inert low/high surface energy, the controlled and precise modulation of the surface chemistry with the desired functional groups is another emerging alternative to attain smart and advanced bio-inspired liquid wettability. [21][22][23][24][25][26][27][28][29] In this context, recently, chemically reactive interfaces were introduced following facile chemistries including UV-assisted click chemistries, [21][22][23] azlactone ring opening reaction, [24][25][26] and Michael addition reaction, [27][28][29] as shown in Fig. 1C.…”
Section: Introductionmentioning
confidence: 99%
“…By patterned treatment/modification of micro‐/nanostructured surface, surface with patterned (super)wettability (SPW) emerged as a superior platform to generate and support the droplet (micro)array . For a typical SPW, droplet (micro)array is expeditiously formed when a “mother droplet” is passively rolled or slipped across the surface, and the dispensed numerous tiny droplets are captured by the patterned (super)hydrophilic (micro)reservoirs due to the wettability boundaries . Compared to conventional droplet (micro)array devices with physical compartments, such as microtiter plates, droplet‐based microfluidics, SPW holds several advantages: 1) Rapid and automated droplet (micro)array formation, which can greatly simplify the handling process and avoid pipetting tools and operations ( Figure a).…”
Section: Applicationsmentioning
confidence: 99%
“…[255][256][257][258] For a typical SPW, droplet (micro)array is expeditiously formed when a "mother droplet" is passively rolled or slipped across the surface, and the dispensed numerous tiny droplets are captured by the patterned (super) hydrophilic (micro)reservoirs due to the wettability boundaries. [259][260][261][262] Compared to conventional droplet (micro)array devices with physical compartments, such as microtiter plates, droplet-based microfluidics, SPW holds several advantages: 1) Rapid and automated droplet (micro)array formation, which can greatly simplify the handling process and avoid pipetting tools and operations (Figure 15a). 2) The position, geometry, amount and size of the (micro)reservoir could be precisely adjusted and organized by intelligent and flexible design of the (super)wettability patterns (Figure 15b).…”
Section: Droplet (Micro)arraymentioning
confidence: 99%